Peningkatan Keterampilan Menulis Teks Prosedur pada Pembelajaran Bahasa Indonesia dengan Model Somatic Auditory Visual Intellectual pada Siswa Kelas IV SD Negeri 01 Sungai Bermas Kabupaten Pasaman Barat - Andini, Amelia; Suriani, Ari (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve procedural text writing skills using the Somatic Auditory Visual Intelectual (SAVI) learning model in grade IV of SD Negeri 01 Sungai Beremas, West Pasaman Regency. The type of research used is Classroom Action Research and is carried out in two cycles with the stages of planning, implementation, observation and reflection. The research subjects were grade IV students of SD Negeri 01 Sungai Beremas, with data collected through test and non-test techniques, while research instruments were through test sheets and non-tests. Data analysis was carried out in a descriptive manner. The results show that the use of the SAVI model can significantly improve procedural text writing skills. First, in the first cycle, the average score in the aspect of the Teaching Module 90 with qualification (A) increased, which increased in cycle II, namely obtaining an average of 95 with qualification (A). The results of the observation of the teacher aspect and the student aspect of the first cycle of the first meeting obtained the same score, namely 83.33 with good qualifications (B) and increased in the first cycle of the second meeting to 87.5 in the aspect of teachers and students. The average score for teacher and student activities in the first cycle of meetings I and II was 85.41 with Good (B) qualifications. In the second cycle, scores for teacher activities were obtained of 95.83 and student activities of 95.83 with very good qualifications (A).